2015
DOI: 10.1186/s12943-015-0336-y
|View full text |Cite
|
Sign up to set email alerts
|

SapC-DOPS nanovesicles induce Smac- and Bax-dependent apoptosis through mitochondrial activation in neuroblastomas

Abstract: BackgroundHigh toxicity, morbidity and secondary malignancy render chemotherapy of neuroblastoma inefficient, prompting the search for novel compounds. Nanovesicles offer great promise in imaging and treatment of cancer. SapC-DOPS, a stable nanovesicle formed from the lysosomal protein saposin C and dioleoylphosphatidylserine possess strong affinity for abundantly exposed surface phosphatidylserine on cancer cells. Here, we show that SapC-DOPS effectively targets and suppresses neuroblastoma growth and elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Importantly, the higher the PS expression on the surface of a cell, the more effectively SapC-DOPS binds to the cell and triggers the ceramide cascade, ultimately resulting in apoptosis ( Fig. 1) [15,26]. Binding of SapC to PS is favored at acidic pH.…”
Section: Sapc-dopsmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, the higher the PS expression on the surface of a cell, the more effectively SapC-DOPS binds to the cell and triggers the ceramide cascade, ultimately resulting in apoptosis ( Fig. 1) [15,26]. Binding of SapC to PS is favored at acidic pH.…”
Section: Sapc-dopsmentioning
confidence: 99%
“…Studies in neuroblastoma reveal that SapC-DOPS-induced apoptosis involves cytosolic release of second mitochondria-derived activator of caspases (Smac) and cytochrome c, as well as mitochondrial translocation and polymerization of Bax (Fig. 1) [26]. Studies of saposin C membrane fusion revealed that although saposin C-induced fusion occurred with a mixture of anionic saturated and unsaturated acyl chains, the fusion process was much slower than that with synthetic unsaturated DOPS, thus DOPS enhances saposin C fusion, especially at acidic pH [30].…”
Section: Sapc-dopsmentioning
confidence: 99%
See 3 more Smart Citations